ADJUVANT CHEMORADIOTHERAPY WITH LOCAL HYPERTHERMIA IN COMBINED TREATMENT OF PRIMARY GLIOBLASTOMA: PRELIMINARY RESULTS - A. I. Ryabova; V. A. Novikov; O. V. Gribova; E. L. Choynzonov; Zh. A. Startseva; E. E. Bober (Сибирский онкологический журнал)
A new technique of concurrent chemoradiotherapy and local electromagnetic hyperthermia for treatment of patients with newly diagnosed glioblastoma was developed at the Cancer Research Institute of Tomsk National Research Medical Center. A total of 20 patients with glioblastoma received concurrent chemoradiotherapy with temozolamide and local hyperthermia. Local hyperthermia was performed using the Celsius TCS device, 2 times a week (8–10 sessions). All patients tolerated the treatment well. The most common toxicity profile of concurrent thermochemoradiotherapy with temozolamide was hematological and neurological. It should be noted that no neurological toxicity was found in randomized trials of chemoradiotherapy with temodal. If the predominant hematologic toxicity might be associated with a small sample of patients in the study, the neurologic toxicity was likely to be related with greater toxic effects of chemotherapy on the brain during local hyperthermia, however, the causes of neurological toxicity during adjuvant chemotherapy courses at the moment we can not explain. Short-term results of concurrent thermochemoradiotherapy demonstrated the objective response rate of 70 %, however, adjuvant chemotherapy produced an increase in the incidence of disease progression during adjuvant chemotherapy. One-year recurrence-free survival rate was 53.3 ± 13.3 %, with a median time to progression of 10.5 months. One-year overall survival rate was 91.7 ± 8 % at a median follow-up time of 9 months. The median overall survival was not reached. A short follow-up time did not allow us to make conclusions about the impact of local hyperthermia on the treatment outcomes. However, there was a tendency towards increase in recurrence-free and overall survivals in patients with newly diagnosed glioblastoma.